Airglow and other F-layer variations in the Indian sector during the geomagnetic storm of February 5-7, 2000 - Mukherjee, G.K. (My University, 2006)
A CCD based all-sky imaging system was used to monitor various nightglow emissions (OI 630-nm, OI 557.7-nm, OI 777.4-nm, Na (589.3-nm) and hydroxyl (OH) airglow) at a low latitude station, Kolhapur (16.8°N, 74.2°E, dip lat 10.6°N) in India to study the characteristics of night airglow variations observed during the period of a moderate/weak geomagnetic storm with SSC (Storm Sudden Commencement) commencing at 15:42 UT (21:12 IST (Indian Standard Time = UT +5 5 hrs)) on February 5, 2000. The images on the night of February 6 show the development of strong ionization anomaly (EIA) with bright intensity regions in OI 630-nm and the signature of rising bubbles with very low intensity. Though the signature of ionospheric plasma bubbles were not observed on the night of February 7, the OI 630-nm images showed the presence of large scale enhanced airglow moving to the southeast direction. The speed was significantly fast (~300 m/s). There were bright intensity regions also observed in OI 557.7-nm airglow, but no intensity enhancement was seen in other mesospheric emissions (Na (589.3-nm) and hydroxyl (OH) airglow ) during this magnetic disturbance. The ionosonde observations at the nearby station, Visakhapatnam (lat. 17.67°N, long. 83.32°E) also showed enhancement in electron density parameter ((foF2)2)atthe station on each night compared to the night of February 4-5 (quiet day) around the same time interval maximizing around 23:00 IST on the night of February 7. The Total Electron Content (TEC)fluctuations obtained from GPS phase delays between two L-band signals (L1 = 1575 MHz and L2 = 1227 MHz) showed no enhancement at night at four mid latitude stations in Japan. However, noontime TEC values were enhanced on February 6 and 7 with maximum intensity occurring on February 7. It is inferred that enhanced storm time effects in the ionosphere were mainly confined to the low latitude region, the effects were subdued in the mid latitude stations.
Keywords: Ionosphere; Equatorial ionosphere; Ionospheric irregularities; Electric fields and currents; F-layer; Geomagnetic storm; Hydroxyl (OH)